A corequisite pathway for mathematics: pairing a developmental lab with a gateway course - Atkins, Charlene (Kansas State University, 2016)
Low success rates in developmental mathematics courses have caused a growing concern for many institutions including moderately selective four-year universities. As a result, institutions have adopted various course redesign models, such as the emporium and replacement models, which take advantage of interactive online learning tools. Though these models have proven successful for increasing completion rates in algebra intensive courses, the models do not address additional concerns for developmental students enrolled in liberal arts mathematics courses. The co-requisite model of instruction is an alternative pathway for students with developmental needs. This model allows students to enroll in the required general education gateway mathematics course concurrent with a developmental mathematics lab, which offers student-centered instruction and just-in-time support for student learning. This study examined the implementation of a co-requisite model of instruction, at one moderately selective four-year university, by investigating the potential of multiple variables for predicting student success.
Keywords: Co-requisite; Developmental Education; Mathematics; Placement